Analysis of Economic Motivation When Individuals Choose an Educational Path - Koksharov, Viktor Anatolyevich; Agarkov, Gavriil Aleksandrovich (Economy of Regions, 2015)
The authors consider the economic motivations when individuals choose an educational path. This line of research is relevant from both, the point of view of science - research of economic behavior of an individual, and the point of view of practice - allows to increase efficiency of investments in a human capital. The authors have developed the economic and mathematical model of choice of optimum educational paths by individuals. The model is realized in the software and approved on real data on more than 5,5 thousand students. For the analysis of the importance of rational economic expectations when an educational path has to be chosen, the paths chosen by students is compared and the educational paths optimum from the point of view of economic rationality are calculated. The analysis of the results has showed that mainly, the choice of educational paths happens according to the economic motivations. On the considered selection, 66 % of prospective students have chosen an optimum path from the point of view of economic preferences. The most significant factor providing development of optimum educational paths is an expectation of higher income upon completion of education - 22 % of all educational paths, and a possibility of cost-cutting of educating or state-subsidized education - 12 %. In our opinion, one of the most important practical results of the research of optimum educational path is the need to consider expectations of students and prospective student when developing a state policy of investment in human capital.